The Birds and the Bees: A Phenomenological Inquiry on Parental Sex Education - Macalipat, Moctar; Nieve, Blaise (Celebes Nursing Journal, 2025)
Introduction: The increasing incidence of adolescent pregnancies underscores the critical need for parental involvement in providing sex education. Objective: This study explored the lived experiences, challenges, and insights of parents in educating their adolescent children about sex-related topics. Methods: A descriptive phenomenological approach was employed, with ten purposively selected parents from Kabacan, North Cotabato serving as key informants. Participants met the following criteria; having adolescent children, experience in providing sex education, and residency in the area. Data were gathered through in-depth interviews and analyzed using Colaizzi’s seven-step method. Results: Thematic analysis revealed three major emergent themes: Parents’ Rendezvous in Sex Parenting, Overcoming Obstacles in Sex Parenting, and Sex Parenting Enlightenment. These encompassed subthemes such as serious conversations, feelings of discomfort, proper timing and discourse, learning from experience, and the need for professional guidance. Parents expressed both confidence and uncertainty in navigating conversations about sex, emphasizing the value of persistence, warmth, and support from healthcare professionals, particularly nurses. Conclusion: The findings affirm that parental sex education fosters communication, trust, and informed decision-making, which are essential in preventing premarital sex, early pregnancy, and early marriage. This study advocates strengthened collaboration between parents and healthcare professionals to enhance the sexual health literacy of adolescents and promote responsible behaviors